2011
DOI: 10.4999/uhod.09098
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Bronchoalveolar Lavage Performed Before and After Bronchoscopic Biopsies to the Diagnosis of Peripheral Lung Cancer

Abstract: The sensitivity of all fiberoptic bronchoscopic techniques in case of a peripheral lung cancer is 69%. In the study, it was aimed to assess the contribution of broncoalveolar lavage (BAL) performed before and after standard biopsy procedures in the diagnosis of peripheral lung cancer. The patients with peripheral lung lesion in radiology, and normal bronchoscopic findings were included in the study, prospectively. BAL was performed in all patients additionally standard biopsy procedures (forceps biopsy, bronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Similar male preponderance of bronchial carcinoma were reported in several other studies. 3,23,28,29 Male-Female ratio in this study is markedly increased which can be explained by some reasons like small sample size, less reporting of female patients in a tertiary care hospital and less common smoking habit in female in our country.…”
Section: Discussionmentioning
confidence: 89%
“…Similar male preponderance of bronchial carcinoma were reported in several other studies. 3,23,28,29 Male-Female ratio in this study is markedly increased which can be explained by some reasons like small sample size, less reporting of female patients in a tertiary care hospital and less common smoking habit in female in our country.…”
Section: Discussionmentioning
confidence: 89%
“…This is similar to Tartar et al who found BAL cytology alone diagnostic for one case in his study. 5 The reason for negative FNA may be inappropriate localization of lesion during FNA procedure.…”
Section: Resultsmentioning
confidence: 99%
“…from all 30 patients with primary lung cancer only one patient had positive sputum cytology. [ 6 ] Our study also showed that this technique is only occasionally used in the diagnosing process and it is the right approach because of their low diagnostic rate.…”
Section: Discussionmentioning
confidence: 65%